Model Pembelajaran Bahasa Arab di Pesantren Salafi dan Khalafi: Studi Pebandingan Terhadap Pesantren Salafiyah Syafi’yah Pohuwato dan Pesantren Hubolo Tapa - Syindi Oktaviani R Tolinggi (LP2M IAIN Sultan Amai Gorontalo, 2020)
This study aims at finding out more deeply how the Arabic learning method in Salafi-style boarding school and Khalafi-style boarding school. This study selected Salafiyah Syafi`iyah boarding school in Pohuwato and Hubulo boarding school in Tapa, Gorontalo as the location. This study is field research using qualitative research methods. As the main instrument, the researchers used other instruments to collect data in the form of observation sheets, interview guidelines and documents. The subjects of this study were Arabic language teachers, students and Pesantren’s Leaders. Data analysis techniques used data reduction, data display and conclusion and verification. The results of this study indicated that the Salafiyah Boarding Shool Pohuwato is a Salafi-style Boarding School. Arabic instruction in this boarding school focuses on grammatical competence or language structure (Nahwu & Sarf) which is applied in the study of the bare book. The learning method used traditional learning methods, such as Sorogan, Bandongan, Wetonan, Pesantren Kilat. While the Hubulo boarding school Tapa is a khalafi-style with active Arabic learning that is not only theory and learning grammar rules, but the also implemented the communcative langauage teaching by practicing daily vocabulary building , daily conversation routine, daily expressions, and Arabic speech training.